Relationship between serum zinc and homocysteine in children with nephrotic syndrome - Welli Hamik; Dany Hilmanto; Sri Endah Rahayuningsih (Indonesian Pediatric Society, 2019)
Background In children, most idiopathic nephrotic syndrome (NS) is a minimal lesion, which responds well to steroids. Hyperhomocysteinemia is pathologic and worsens NS by causing chronic inflammation, leading to glomerular sclerosis. Zinc metalloenzymes are involved in homocysteine metabolism. Objective To assess for a possible relationship between serum zinc and homocysteine in children with NS. Methods A cross-sectional study was conducted in children with NS aged 1-18 years, who were admitted to Hasan Sadikin Hospital from November 2017 - January 2018. Subjects were selected consecutively. Serum zinc and homocysteine were measured in all subjects. Statistical analysis was done with Pearson's correlation test. If the distribution was not linear, the analysis was continued with non-linear regression. Results There were 23 children who met the inclusion criteria. Mean serum homocysteine and zinc levels were 10.37 (SD 4.11) Âµmol/L and 51.13 (SD 29.69) Âµg/dL, respectively. Pearson's correlation analysis showed no linear correlation between them (r coefficient -0.173; P=0.430). However, after adjusting for age and serum albumin level, multiple regression analysis suggested a cubical relationship between serum homocysteine and zinc, using the equation: homocysteine = -4.572 + 0.735 x zinc - 0.0012 x zinc2 + 0.00005 x zinc3 x age (months) (R2 multiple=53.2%; P=0.012). This equation indicates that 53.2% of homocysteine variation was influenced by serum zinc concentration. Conclusion In childhood NS, homocysteine is not correlated linearly with zinc, but related with cubical model.